Ambulatory Training for Primary Care General Internists: Innovation With the Affordable Care Act in Mind - Rieselbach, Richard E. (The Accreditation Council for Graduate Medical Education, 2014)
BACKGROUND: Although primary care general internists (PCGIs) are essential to the physician workforce and the success of the Affordable Care Act, they are becoming an endangered species. OBJECTIVE: We describe an expanded program to educate PCGIs to meet the needs of a reformed health care system and detail the competencies PCGIs will need for their roles in team-based care. INTERVENTION: We recommended 5 initiatives to stabilize and expand the PCGI workforce: (1) caring for a defined patient population, (2) leading and serving as members of multidisciplinary health care teams, (3) participating in a medical neighborhood, (4) improving capacity for serving complex patients in group practices and accountable care organizations, and (5) finding an academic role for PCGIs, including clinical, population health, and health services research. A revamped approach to PCGI education based in teaching health centers formed by community health center and academic medical center partnerships would facilitate these curricular innovations. ANTICIPATED OUTCOMES: New approaches to primary care education would include multispecialty group practices facilitated by electronic consultation and clinical decision-support systems provided by the academic medical center partner. Multiprofessional and multidisciplinary education would prepare PCGI trainees with relevant skills for 21st century practice. The centers would also serve as sites for state and federal Medicaid graduate medical education (GME) expansion funding, making this funding more accountable to national health workforce priorities. CONCLUSIONS: The proposed innovative approach to PCGI training would provide an innovative educational environment, enhance general internist recruitment, provide team-based care for underserved patients, and ensure accountability of GME funds.